MODEL PEMBIAYAAN SYARIAH POLA KEMITRAAN ANTARA BSI DENGAN UMKM MITRA PESANTREN DAARUL ULUUM BOGOR - Apriyana, Maya; Hasbi, Sahlan; Apriliansyah, Muhammad Romi; Umar Ali, Rizki (PROFJES: Profetik Jurnal Ekonomi Syariah, 2024)
In its evolution and role, Bank Syariah Indonesia (BSI) is one of the sharia financial entities that organizes financing programs to support the growth of micro entrepreneurs. One of these programs is financing for Micro, Small and Medium Enterprises (MSMEs) assisted by Islamic boarding schools and MSMEs around the Islamic boarding school area, with the aim of increasing financial access in the area. The aim of this research is to understand the sharia financing model implemented in the partnership between BSI and the Daarul Uluum Bogor Islamic boarding school in supporting the Islamic boarding school partner business community, evaluate the effects of sharia financing, and explore the potential for replicating the sharia financing model at the Daarul Uluum Lido Islamic boarding school. This research uses a qualitative approach with data collection methods through interviews, observation and documentation. The data analysis technique refers to the Miles and Huberman model which includes three steps: data reduction, data presentation, and conclusion verification. Research findings show that the sharia financing model implemented by BSI with the partner business community of Pesantren Daarul Uluum Bogor is through the murabahah bil wakalah financing scheme. Sharia financing from BSI has had a positive impact on BSI, the Daarul Uluum Bogor Islamic boarding school, and the Islamic boarding school partner business community. Apart from that, this sharia financing model has great potential to be replicated at the Daarul Uluum Lido Islamic boarding school, supported by the internal experience of Islamic boarding school administrators in managing the economy and the significant number of potential customers from the Islamic boarding school partner business community.